Pengaruh Penerapan Permainan Tradisional Dalam Pendidikan Jasmani Terhadap Motivasi Belajar Siswa Sekolah Menengah Atas - Sulthan Dhia Anugrah; Febi Kurniawan; Muhammad Mury Syafei (Peneliti.net, 2023)
The problem of this research is is there the influence of the application of traditional games in physical education on the learning motivation of high school students? The research objective was to determine the effect of implementing traditional games in physical education on high school students' learning motivation. Experiment is the method used in this study and uses a quantitative approach. The samples used were 32 students using a sampling technique using cluster random sampling. The data collection technique used in this research is to use an experimental technique, using a motivational questionnaire by means of pretest-posttest. From the results of this study it is known that the significance value (2-tailed) of this case example is 0.000 (p <0.05) so that the results of the pre-test and post-test have significant changes (meaning). Based on the descriptive statistics of the pre-test and post-test, it is proven that the final test is higher. It can be concluded that the use of traditional game methods in physical education learning has an influence on student learning motivation.